CTIM-01. GLIOBLASTOMA RE-IRRADIATION: IMPACT OF CONCOMITANT CHEMOTHERAPY. (9th November 2020) - Epaillard, Nicolas; Hammoudi, Nassim; Faron, Matthieu; ammari, Samy; Pallud, Johan; Louvel, Guillaume; Lezghed, Naima; Garcia, Gabriel; Bockel, Sophie; Copaciu, Razvan; Dezami, Edouard; Knafo, Steven; et al.
Abstract: PURPOSE: Although the standard of initial treatment is well defined for glioblastoma, no recommendation exists in the relapse setting. This work focuses on the optimal strategy for recurrent glioblastoma. METHODS: Retrospective monocentric analysis of all recurrent glioblastoma adult patients treated since 2000 in one center by re-irradiation, alone or combined with chemotherapy and/or surgery at first or second relapse. RESULTS: Patient (n=61) median age was 55 (27 to 76), 44% were women. At diagnosis, 77% underwent surgical resection and 23% were biopsied. Most (95%) received a Stupp regimen. After a median follow-up of 31.1 months, 44 patients (72%) had died, median overall survival (mOS) was 39.8 months. Regardless of the time of treatment, patients treated with radiotherapy concomitant to bevacizumab (RTbev) showed superior survival data compared to patients treated with radiotherapy alone (RTalone). At first relapse, median progression free survival (mPFS) of RTbev was 9.9 versus 3.6 months for RTalone (OR=3.98 (3.14–61.81); p=0.001). At second relapse, mPFS of RTbev was 9.2 versus 5.4 months for RTalone (OR=2.31 (1.18–7.75); p=0.029), and mOS of RTbev was 15.2 versus 9.1 months for RTalone (OR=3.60 (2.17–18.13); p=0.001). CONCLUSION: This retrospective monocentric analysis reports a favourable impact of bevacizumab adjunction to re-irradiation.